2019
DOI: 10.1088/1755-1315/374/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

Moisture content, color quantification and starch content of oil palm trunk (Elaeis guineensis Jacq.)

Abstract: Research and utilization of oil palm trunk (Elaeis guineensis Jacq.) have not been widely carried out. Knowledge the characteristics of oil palm trunk (OPT) as part of understanding this type for reference to further development. The aim of its study was (1) to determine the value of moisture content (MC) in fresh condition after cutting, (2) to quantify the color value (E), (3) to quantify the color change value (ΔE) in transverse and longitudinal cross-section and (4) to measure the percentage of starch cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In this study, the color values of laccase are related to lightness and yellowness values. Other studies have found a correlation between increased lightness (L) and yellowness (b) and higher E values, but not redness (a) levels (Bahanawan et al 2019).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In this study, the color values of laccase are related to lightness and yellowness values. Other studies have found a correlation between increased lightness (L) and yellowness (b) and higher E values, but not redness (a) levels (Bahanawan et al 2019).…”
Section: Discussionmentioning
confidence: 82%
“…Laccase color, functional groups, enzyme activity, protein content, and enzyme-specific activity were characterized. The colors of laccase analysis were conducted according to Bahanawan et al (2019). The color of the enzymes produced was compared to commercial enzyme color and the absorbance of The functional groups of the crude laccase were analyzed based on the procedure used by Samui and Sahu (2018) and Yanto et al (2021) using Fourier Transform Infrared (FTIR) (Perkin-Elmer) at 400-4,000 nm and 32 scans.…”
Section: Laccase Characterizationmentioning
confidence: 99%
“…However, the utilization of felled OPT has not been established, and those are left in the plantations. The green moisture content of the OPT is very high and contains a lot of sugars (Tomimura 1992a ; Bahanawan et al 2019 ). As a result, the left OPT tends to rot, causing various problems, including problems caused by pests (Abdullah et al 2012 ; Pulingam et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Along the height, they show an obvious increase from bottom to top (Lim and Khoo 1986 ). Vascular bundles are stiffer and stronger than parenchyma (Rich 1987 ; Bahanawan et al 2019 ). Parenchyma cells are primarily responsible for the storage function of nutrients, especially starch.…”
Section: Introductionmentioning
confidence: 99%